Telaah Bisnis Penerbangan Komersial Di Indonesia Setelah Terbit UU Penerbangan No.1/Th 2009 - arista atmadjati; normalisa (Liaison Journal of Engineering, 2022)
After the launch of aviation law number 1 of 2009 by the government, of course, the hope of the Indonesian people that the atmosphere of commercial flights in Indonesia will be increase and guaranteed that the safety factor will improve and be accompanied by an increasingly better quality of service in accordance with the spirit of the consumer protection law number 1 of 1999. Consumer rights are the most Priority in the issuance of aviation law. Many airlines ignored the issue of long delays, changing flight schedules, and lost passengers' items of baggage as well. With the aviation law 1/2009, it is hoped that all of the above problems will subside because if the airline is reputable, it can be subject sanctions up to the heaviest revocation of flying permits for certain, fatal revocation of the Air Operator Certificate. However, since the issuance of Law 1/2009, the government has also been miss conduct by the bankruptcy of the state-owned airline Merpati Nusantara, which should have been avoided. We hope that all of us stakeholders of aviation in Indonesia will become loyal customers to board the Indonesia domestic airlines as their choosing transport and the airlines can improve the level of service and maintain the level of safety.Keywords: keep safe flights, serve customers, keep the fleet growing increase